Letter from Charles Coulson to Harrison Shull, 1967 - Coulson, C. A. (Charles Alfred) (1967)
Concerns Coulson's appreciation for Shull's work on the Quantum Chemistry Program Exchange (QCPE) Newsletter.
Keywords: ALGOL (Computer program language); Shull, Harrison; FORTRAN (Computer program language); Mathematicians; Chemists; Quantum chemistry; Coulson, C. A. (Charles Alfred), 1910-1974